PENGEMBANGAN E-FLIPBOOK PADA PENGETAHUAN DIABETES MELITUS TIPE 2 DENGAN AKTIVITAS FISIK PADA REMAJA SMAN 15 BANDUNG - Kasyf, Ahmad Ryadhian; Setiawan, Ridwan (Jurnal Kesehatan Siliwangi, 2024)
Diabetes Mellitus or what is called and abbreviated to (DM) is also recognized as "the silent killer" is a chronic disease. The number of DM sufferers in Indonesia is predicted to reach 28.57 million in 2045. The number of DM sufferers in Indonesia is predicted to reach 28.57 million in 2045. Education using e-flipbook media regarding physical activity is one of the measures preventive in preventing type 2 DM in adolescents. Objective: Develop e-flipbook media regarding prevention of type 2 DM with physical activity in adolescents at SMAN 15 Bandung with research into the development of the ADDIE model. Methodology: The type of research is R&D (Research and Develop). The population was 404 class X students at SMAN 15 Bandung using proportionate random sampling technique. Results: E-flipbook media with a horizontal shape and dimensions of 16.26 x 9.14 cm which can be accessed via the Hyzne website. obtained a score of 91% in the "very feasible" category from material experts, 100% in the "very feasible" category from media experts and 89.7% in the appropriate category from small-scale trials. There is an influence of e-flipbook media with an increase of 34.17%. Conclusion: The e-flipbook media contains material about type 2 diabetes mellitus and Artificial Intelligence (AI) images created by yourself, with bright colors. The media was declared to be "very feasible" by experts and there was an influence of providing e-flipbook media regarding type 2 diabetes mellitus.